Concurrent Stunting with Overweight in High School Students from EslamAbad-e Gharb City, Iran - B Sahargahi; SM Nachvak; H Abdollahzad; A Tandorost; J Moludi; M Rezaei; MR Naderi (Armaghane Danesh Bimonthly Journal, 2021)
Background & aim: Concurrent stunting with overweight" is one of the consequences of nutritional transition, which has worsened the outcomes more than overweight itself. The aim of this study was to determine the trend of anthropometric indices in primary to high school students in Eslam Abad-e Gharb city, Iran.